The spread of the VO pattern in subject relative clauses: The OV/VO alternation in Old and Middle English - Bloom, Barthe (Studying Language Change in the 21st Century: Theory and Methodologies, 2022)
This study investigates the change from object-verb to verb-object word order in Old and Middle English subject relative clauses and aims to shed light on the questions i) What underlies the alternation between the two word order patterns in Old and Middle English subject relative clauses?, and ii) Why did these clauses change their preference? Concerning the first question, the study confirms by means of random forests and variable importance that the principle of end-weight determines OV/VO word order in Old English. In addition, the relativizer is identified as an important factor. In Middle English, both factors are not as relevant and the postverbal slot can be filled with short objects as well. Based on the initial importance of the relativizer, it is hypothesized that analogy to the main clause facilitates VO word order in subject relative clauses. Two predictions that follow from this hypothesis are tested and confirmed. Firstly, subject relative clauses that were similar to main clauses are shown to have a higher proportion of VO than ones that were not similar to main clauses. Secondly, the effect of the end-weight principle is shown to be weaker in relative clauses with a high resemblance to main clause
Keywords: analogy; Old English; Middle English; subject relative clauses; word order; language change